1998
DOI: 10.2214/ajr.170.5.9574613
|View full text |Cite
|
Sign up to set email alerts
|

Helical CT versus CT arterial portography in the detection of hepatic metastasis of colorectal carcinoma.

Abstract: OBJECTIVE.The study is a prospective comparison of helical CT with nonhelical CT ar- CT and CTAP on a segment-by-segment basis with a five-level scale of confidence.Results were analyzed by receiver operating characteristic methods. RESULTS.The results of the histologic study disclosed 50 metastatic lesions. Helical CT CONCLUSION.Helical CT is superior to nonhelical CTAP in the detection of hepatic metastases from colorectal carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
8

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(25 citation statements)
references
References 28 publications
0
17
0
8
Order By: Relevance
“…The presence and locations of extracolonic metastases were recorded. The radiologists diagnosed extracolonic metastasis using previously published established criteria [15,16].…”
Section: Image Analysismentioning
confidence: 99%
“…The presence and locations of extracolonic metastases were recorded. The radiologists diagnosed extracolonic metastasis using previously published established criteria [15,16].…”
Section: Image Analysismentioning
confidence: 99%
“…Underestimation of HCC extension results in early recurrence, and imaging procedures to detect tiny HCC lesions prior to treatment are important. Several studies have reported that CTAP is considered to be the most sensitive technique for the detection of hepatic tumors [13,14], however, this technique is costly, invasive and has a high false-positive rate [15,16]. There are several studies indicating that the combined use of CTAP and CTHA for patients with cirrhosis would be helpful in accurate diagnosis of small nodules [19][20][21][22], and is beneficial in the preoperative evaluation of patients with HCC [23].…”
Section: Discussionmentioning
confidence: 99%
“…Among these imaging techniques, CTAP is one of the most sensitive techniques available for detecting hemodynamic change [13,14], while its distinct disadvantages include invasiveness, high cost and a high rate of false-positive results [15,16]. We have frequently observed that some of the hepatic lesions identified by CTAP and/or CTHA in HCC patients are too small to be diagnosed as additional HCC lesions.…”
Section: Introductionmentioning
confidence: 99%
“…B. bei neu ro en dokri nen Tu mo ren, Nie ren zell-und Schilddrü senkar zi no men, Me la no men, Sar komen) und bei Ver dacht auf das Vor lie gen ei nes he pa to zel lu lä ren Kar zi noms so wie zur Cha rak te ri sie rung fo ka ler Le ber lä sionen die Durch füh rung ei ner 2-oder 3-Phasen,Spi ral,CT er for der lich. si ti ven Di ag no sen führ te [22,24]. Mit te der 1990er Jah re konn te erst mals ge zeigt wer den, dass die kon trast mit tel un ter stütz-te MRT im Ver gleich zur CTAP nicht nur eine hö he re Ge nau ig keit in der De tek ti on fo ka ler Le ber lä sio nen auf wies, son dern auch als nichtin va si ves Ver fah ren we sentlich preis güns ti ger ist [20].…”
Section: Abb 1 8 Dar Stel Lung Der Ge Fäß Ana To Mie Der Le Ber (A) unclassified